A qualitative study of health‐care experiences and challenges faced by ageing homebound adults - Joyce M. Cheng; George P. Batten; Thomas Cornwell; Nengliang Yao (Wiley, 2020)
Abstract Background The ageing of the global population is associated with an increasing prevalence of chronic diseases and functional impairments, resulting in a greater proportion of homebound individuals. Objective To examine the health‐care experiences of older homebound adults who have not previously received home‐based primary care (HBPC). To explore their impressions of this method of care. Design Cross‐sectional qualitative study using semi‐structured interviews. Setting and Participants 18 older homebound individuals in Central Virginia. Results Our findings revealed that homebound individuals faced significant health challenges, including pain resulting from various comorbidities. They felt that their mobility was restricted by their physical conditions and transportation challenges. These were major barriers to social outings and health‐care access. Participants left their homes infrequently and typically with assistance. Regarding office‐based care, participants were concerned about long wait times and making timely appointments. Some thought that HBPC would be convenient and could result in better quality care; however, others believed that the structure of the health‐care system and its focus on efficiency would not permit routine HBPC. Discussion and Conclusions Older homebound adults in this study faced high burdens of disease, a lack of mobility and difficulty accessing quality health care. Our observations may help researchers and clinicians better understand the health‐care experiences and personal opinions of older homebound individuals, informing the development of effective and empathetic home‐based care. Participant responses illuminated a need for education about HBPC. We must improve health‐care delivery and develop comprehensive, patient‐centered HBPC to meet the needs of homebound individuals.